Occupational exposure and awareness of Occupational safety and health among cloth dyeing workers in Jaipur India - Krishan Kant Upadhyay; Anish Chandra Pandey (Iranian Journal of Health, Safety and Environment, 2016)
Abstract: Objectives: We assessed the health risk factors and awareness of Occupational safety and health of workers in cloth dyeing industry of Jaipur. Methods: A pretested questionnaire was used to evaluate the health problems and awareness of occupational safety and health among workers. Results: The majority of these workers were suffering from eye irritation, back pain, allergies, general weakness, with most workers having three to five of these health problems. Our study reported higher incidence of musculoskeletal and respiratory diseases among workers in different age groups. Conclusion: A large number of diseases in different age groups is an indication that this industry exposes workers to many health hazards and lack of awareness and non availability of PPE in this industry is aggravating the health problems of the workers.